2019
DOI: 10.1002/app.47943
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a novel inherently flame‐retardant rigid polyurethane foam composite bearing imide and oxazolidinone

Abstract: A novel inherently flame-retardant rigid polyurethane (PU) foam with imide and oxazolidinone was prepared by using 3,3 0 ,4,4 0biphenyltetracarboxylic dianhydride (PTDA) and 9,10-dihydro-9-oxa-(10-glycidoxypropylene)-10-phosphap-henanthrene-10-oxide (e-DOPO) as reactive flame retardants. The physical and mechanical properties of the prepared PU foams were investigated. The compressive strength was improved to 0.22 MPa, the thermal conductivity decreased, and the density hardly changed. Thermogravimetric (TG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The phosphorous based polyols could be mixed with bio-based polyols to prepare highly fire retardancy and superior physico-mechanical rigid PU foams [75]. The study of a rigid PU foam showed that 3,3',4,4'-biphenyltetracarboxylic dianhydride and 9,10-dihydro-9-oxa-(10-glycidoxypropilene)-10-phosphaphenantrene-10-oxide lead to an increase in graphite in the fire residue and the formation of a better barrier to prevent burning by the condensed phase mechanism [76]. Rigid PU modified with microencapsulated red phosphorous, Mg(OH)₂, glass filler and hollow glass bead were prepared and showed that the fire retardancy and the combustion were improved [77].…”
Section: Flammabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorous based polyols could be mixed with bio-based polyols to prepare highly fire retardancy and superior physico-mechanical rigid PU foams [75]. The study of a rigid PU foam showed that 3,3',4,4'-biphenyltetracarboxylic dianhydride and 9,10-dihydro-9-oxa-(10-glycidoxypropilene)-10-phosphaphenantrene-10-oxide lead to an increase in graphite in the fire residue and the formation of a better barrier to prevent burning by the condensed phase mechanism [76]. Rigid PU modified with microencapsulated red phosphorous, Mg(OH)₂, glass filler and hollow glass bead were prepared and showed that the fire retardancy and the combustion were improved [77].…”
Section: Flammabilitymentioning
confidence: 99%
“…After a surface modification EG was introduce also in foams based on PU-imide. The foams exhibited outstanding enhancements compare to that of only pristine EG introduction in compressive strength, thermal stability and flame resistance [86]. Four wood-based wastes were incorporated into rigid bio-based PU foams; these were characterized by thermal and combustion properties.…”
Section: Flammabilitymentioning
confidence: 99%
“…Recently, many flame retardants on fire resistance of PUF have been reported 11,13–15 . The selection of suitable flame retardants is extremely important for enhancing the flame retardancy of materials.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Recently, many flame retardants on fire resistance of PUF have been reported. 11,[13][14][15] The selection of suitable flame retardants is extremely important for enhancing the flame retardancy of materials. For example, some researchers have adopted additive flame retardants, such as halogenated compounds, 16 graphite, [17][18][19] phosphorus nitrogen compounds and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…3,3′4,4′‐biphenyltetracarboxylic dianhydride and 9,10‐dihydro‐9‐oxa‐(10‐glycidoxypropylene)‐10‐phosph‐phenanthrene‐10‐oxide were incorporated in RPUF for enhancing the flame retardancy of the foam. It was concluded from the results that the incorporated flame retardant showed a small improvement in the thermal properties but the peak of heat release (PHRR) and total heat release (THR) decreased by approximately 20% . Along with the incorporation of flame retardant, some functional filler such as aluminium diethyl phophinate, calcium hypophosphite, and others may also be used to abate the flammability of RPUF.…”
Section: Introductionmentioning
confidence: 99%